ANALISIS PENGARUH BUDAYA ORGANISASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING (Studi Kasus pada PT. LG Bagian Penjualan Indonesia Semarang) - Arta Graha, Alexander Monte Christo; Rahardjo, Edy (Faculty of Economics and Business Diponegoro University, 2016)
The problems that occurred in the employee portion of sales LG Indonesia Semarang is a decline in performance is indicated by not achieving the target for 2015. The employee performance and motivation is also thought to be influenced by factors of organizational culture and also compensation deemed not feasible by most employees. This study aimed to analyze the influence of organizational culture on the motivation and compensation and employee performance parts sales LG Indonesia Semarang. The population used in this study were all employees of LG Indonesia Semarang. The sampling technique used was purposive sampling. Criteria samples taken were all employees of the sales department LG Indonesia Semarang who have worked more than two years are 71 nurses. The method of collecting the data in this study using questionnaires and interviews. Methods of data analysis using path analysis. Based on the research, organizational culture and compensation have a positive effect on motivation and performance, while motivation is also a positive effect on performance. Based on the results Sobel Test to determine whether there is mediating the relationship between the independent and dependent variables, it is known that motivation mediates the effect of compensation and organizational culture on performance.